Resection Margin Involvement in Pancreaticoduodenectomy. A Single Centre Experience - Buscemi, Salvatore; Taffurelli, Giovanni; D’Ambra, Marielda; Monari, Francesco; Macchini, Marina; Ricci, Claudio; Di Marco, Mariacristina; Santini, Donatella; Pezzilli, Raffaele; Casadei, Riccardo; et al. (JOP. Journal of the Pancreas, 2012)
Context Rates of microscopic margin involvement (R1), after pancreaticoduodenectomy for peri-ampullary cancer, vary markedly from 16% to more than 75% .One of the reasons is the lack of international consensus protocol for the pathological examination. Objectives To evaluate the rates of R1 in patients undergoing pancreaticoduodenectomy for peri-ampullary malignancy after the application of a standardized protocol of specimen’s margination. Methods From January 2010 to May 2012 data regarding 71 patients (Group A) undergoing pancreaticoduodenectomy for periampullary cancer, were collected in a prospective database. In all patients the histological examination was carried out according of a standardized protocol of specimen’s margination. R1 was defined as the presence of microscopic involvement <1 mm from the margin. The rate of R1 was compared with a historical cohort of 23 patients (Group B), undergoing pancreaticoduodenectomy for periampullary cancer without a standardized protocol of margination. The statistical analysis was carried out by using the Fischer exact test, the Pearson chi square test, the t-test and the logistic regression. Results The two groups were similar regarding sex, age, type and extension of resection and histological data (T, N, type of tumor). R1 rate was statistically significant higher in Group A than Group B (89.2% vs. 66.7%, P=0.015). The logistic regression, conducted for all patients, showed that presence of ductal adenocarcinoma or cholangiocarcinoma and T status increased significantly the risk of R1 (OR=41.4, P=0.004 and OR=6.3, P=0.050, respectively). The multivariate analysis including the type of margination showed that also the application of a standardized margination protocol was an independent factor related to R1 (OR=4.3; P=0.030). Conclusion Lack of standardization of pathological examination and controversy regarding the definition of microscopic margin involvement have resulted in variation of reported R1 rates Margin involvement in pancreatic cancer is a frequent and prognostically significant finding when specimens are assessed using a standardized protocol of specimen’s margination.